Giant adiabatic temperature change in FeRh alloys evidenced by direct measurements under cyclic conditions. (March 2016) - Chirkova, A.; Skokov, K.P.; Schultz, L.; Baranov, N.V.; Gutfleisch, O.; Woodcock, T.G.
Abstract: We report on (1) direct measurements of ΔT ad for binary Fe49 Rh51 during field cycling and (2) maximum possible ΔT ad measured under discontinuous protocol. Our results show that the ΔT ad is 9.2 K on the first application of magnetic field of Δμ 0 H = 1.9 T and it remains as high as 6.2 K during the cycling in alternated field of the same magnitude. In addition, the adiabatic temperature change and magnetic entropy change under the first application of magnetic field and under cyclic conditions were determined indirectly using three different approaches: (1) from magnetic measurements ( M(T) H dependences, Maxwell relations), (2) from calorimetry ( C(T) p, H, S-T diagram) and (3) from H-T diagram. While the indirectly measured maximum possible ΔT ad lies in the range of 10.5–12 K, the reduced value of ΔT ad measured directly under cycling (6.2 K) is still extraordinarily high and is 15% higher than in Gd in similar magnetic field. This demonstrates the potential of materials with a first order metamagnetic transition for magnetocaloric applications despite the presence of hysteresis. Graphical abstract: